2021
DOI: 10.1038/s41598-020-80060-3
|View full text |Cite
|
Sign up to set email alerts
|

Ephrin A4-ephrin receptor A10 signaling promotes cell migration and spheroid formation by upregulating NANOG expression in oral squamous cell carcinoma cells

Abstract: Ephrin type-A receptor 10 (EPHA10) has been implicated as a potential target for breast and prostate cancer therapy. However, its involvement in oral squamous cell carcinoma (OSCC) remains unclear. We demonstrated that EPHA10 supports in vivo tumor growth and lymphatic metastasis of OSCC cells. OSCC cell migration, epithelial mesenchymal transition (EMT), and sphere formation were found to be regulated by EPHA10, and EPHA10 was found to drive expression of some EMT- and stemness-associated transcription factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 51 publications
0
15
0
Order By: Relevance
“…A limitation of this study is the lack of molecular mechanisms by which EFNA4 promotes lung cancer metastasis. The present evidence indicates that signaling by EPHA2 and its ligand, EFNA4, promotes hepatocellular carcinoma cell migration and the combination of EFNA4 and EPHA10 promotes proliferation and migration in oral squamous cell carcinoma cells [ 25 , 26 ]. In fact, during the study, we also found the positive relationships between EFNA4 and key glycolytic enzymes (not shown in this paper).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…A limitation of this study is the lack of molecular mechanisms by which EFNA4 promotes lung cancer metastasis. The present evidence indicates that signaling by EPHA2 and its ligand, EFNA4, promotes hepatocellular carcinoma cell migration and the combination of EFNA4 and EPHA10 promotes proliferation and migration in oral squamous cell carcinoma cells [ 25 , 26 ]. In fact, during the study, we also found the positive relationships between EFNA4 and key glycolytic enzymes (not shown in this paper).…”
Section: Discussionmentioning
confidence: 98%
“…Previous studies have shown that members of the ephrin family play an important role in the pattern of nervous system, vascular system assembly and angiogenesis [ 20 , 21 , 22 , 23 , 24 ]. EFNA4 has also been reported to be involved in the proliferation of oral squamous cell carcinoma, hepatocellular carcinoma and gastric cancer [ 25 , 26 , 27 ]. However, the functions and mechanisms of EFNA4 in lung cancer are still not clear.…”
Section: Introductionmentioning
confidence: 99%
“…Distinct from the cell-autonomous mechanistic bases for AVE motility suggested by the above approach, our communication analysis and inhibitor experiments identified novel intercellular signalling pathways that might be involved in the unidirectional migration of the AVE. Ephrins, Semaphorins and their respective cognate receptors are mainly membrane-tethered molecules, that were first identified as axon guidance cues, but have since been shown to regulate migration of other cell types by direct intercellular signalling (Alto and Terman, 2017;Chen et al, 2021;Kania and Klein, 2016;Toyofuku et al, 2004). Given the large number of Ephrin and Semaphorin family members expressed in the early embryo at this stage, a certain degree of functional redundancy is possible.…”
Section: Discussionmentioning
confidence: 99%
“…The analysis of intercellular communication in the scRNAseq data at E5.5 and E6.25 has been performed using a curated list of 2,548 ligand-receptor pairs (LRPs) (Caruso et al, 2020), to which we added the following LRPs based on previously reported direct interactions: CER1-MRC2 (Vento-Tormo et al, 2018), CER1-BMP2/BMP4 (Chi et al, 2011), CER1-NODAL (Aykul and Martinez-Hackert, 2016), LEFTY1-NODAL (Chen and Shen, 2004), LEFTY1-BMPR2 (Zabala et al, 2020). We selected only AVE, emVE and Epi cells, and we filtered out genes detected in fewer than 10 cells or with log-normalized mean expression computed on non-zero values smaller than 1.…”
Section: Cell-cell Communication Analysismentioning
confidence: 99%
“…Previous studies have shown that members of ephrin family play an important role in the pattern of nervous system, vascular system assembly and angiogenesis [20][21][22][23][24]. EFNA4 has also been reported to be involved in the proliferation of oral squamous cell carcinoma, hepatocellular carcinoma and gastric cancer [25][26][27]. However, the functions and mechanisms of EFNA4 in lung cancer are still not clear.…”
Section: Introductionmentioning
confidence: 99%